2005
DOI: 10.1038/sj.ejhg.5201398
|View full text |Cite
|
Sign up to set email alerts
|

Twin study of genetic and aging effects on X chromosome inactivation

Abstract: To investigate the genetic influence on X chromosome inactivation and on age-related skewing of X inactivation, in particular, we analysed the X inactivation pattern (XIP) in peripheral blood cells from 118 young monozygotic (MZ) twin pairs (18-53 years), 82 elderly MZ twin pairs (55 -94 years), 146 young dizygotic (DZ) twin pairs (20-54 years) and 112 elderly DZ twin pairs (64 -95 years). Elderly twins had a higher frequency of skewed X inactivation (34%) than young twins (15%) (Po0.001). Our data suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
113
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(137 citation statements)
references
References 42 publications
21
113
3
Order By: Relevance
“…Age has been shown to have an effect on XCI skewing, but is only significant in females over 55 years of age. 34,35 The mothers in our study sample were aged from 28 to 55, and the age-related increase in degree of skewing is not therefore expected in the sample. This is also true of the patients and controls.…”
Section: Discussionmentioning
confidence: 85%
“…Age has been shown to have an effect on XCI skewing, but is only significant in females over 55 years of age. 34,35 The mothers in our study sample were aged from 28 to 55, and the age-related increase in degree of skewing is not therefore expected in the sample. This is also true of the patients and controls.…”
Section: Discussionmentioning
confidence: 85%
“…[2][3][4]6,20 Furthermore, if only transcription based analysis were to be taken into account, the results obtained in this cohort of aging females and our recently published data obtained in neonates 13 document that the incidence of skewing triples from birth to older age. Further studies on age-dependent skewing may help understand the biology of the aging hematopoiesis, and the pathobiology of hematopoietic malignancies of the elderly.…”
Section: Support For the Acquired Skewing Phenomenonmentioning
confidence: 82%
“…22; 67% in centenarians, ref. 23). Although a recent report suggested that buccal epithelial cells were also subjected to increased skewing with time (24), the incidence of skewing in hematopoietic versus nonhematopoietic tissues of aging individuals is generally poorly correlated (correlation ratio 0.19-0.74) (25)(26)(27) except in some cases of extreme skewing, suggesting a more stable incidence of skewing in nonhematopoietic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Variant alleles of the X chromosome controlling element (Xce) were subsequently found to bias XCI in mice and cause skewing in heterozygous mice, suggesting that primary skewing was genetically controlled, at least in this species (31). In humans, no Xce-like element has been identified to date, though a few isolated reports have favored a genetic influence on primary skewing: (a) a rare mutation in the X (inactive)-specific transcript (XIST) minimal promoter was found to favor primary skewing (32,33); (b) an alteration in X chromosome inactivation center (XIC) was suggested to be responsible for the skewing of XCI observed in 3 related females (34); (c) twin studies reported a good concordance of XCI patterns between monozygous twins (35)(36)(37); and (d) other studies have documented the heritability of the skewing trait (38)(39)(40). Most of these studies either reported rare genetic events or were conducted in blood cells of adult females (likely affected by age-associated skewing).…”
Section: Introductionmentioning
confidence: 99%